2021
DOI: 10.3389/fbioe.2021.807883
|View full text |Cite
|
Sign up to set email alerts
|

Genipin Cross-Linked Decellularized Nucleus Pulposus Hydrogel-Like Cell Delivery System Induces Differentiation of ADSCs and Retards Intervertebral Disc Degeneration

Abstract: Intervertebral disc degeneration (IDD) is the pathological basis of disc degenerative diseases (DDD). Reduction in the number of cells and degeneration of the extracellular matrix (ECM) in the nucleus pulposus (NP) are characteristics of IDD. Bio-hydrogel combined with stem cell transplantation is a promising treatment. Injectable ECM hydrogels have good biological activity and in-situ gelatinization. However, its biomechanics and stability are insufficient to provide adequate mechanical support for interverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…More importantly, compared to other commonly used cross-linking agents, such as glutaraldehyde (GA), carbodiimide, epoxy compounds, etc., genipin is considered to be the least toxic cross-linking agent, which can effectively reduce the immunogenicity of xenogeic matrices (Oryan et al, 2018). In the degenerative intervertebral disc, genipin crosslinked gel is considered degradate more slowly than gel without genipin (Likhitpanichkul et al, 2014;Likhitpanichkul et al, 2015), and the use of genipin crosslinking has been shown to alter several mechanical parameters (Fujii et al, 2020) and may be advantageous in treating disc pain (Guterl et al, 2013;Guterl et al, 2014;Peng et al, 2020) and disc degeneration (Yu et al, 2021). Thus, we tried genipin and tested Fib-T-G (F140 G6) gel as the best consistency for biocompatibility and adhesive strength; afterward, we applied this biological glue to repair the caudal AF slit injury of rats.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, compared to other commonly used cross-linking agents, such as glutaraldehyde (GA), carbodiimide, epoxy compounds, etc., genipin is considered to be the least toxic cross-linking agent, which can effectively reduce the immunogenicity of xenogeic matrices (Oryan et al, 2018). In the degenerative intervertebral disc, genipin crosslinked gel is considered degradate more slowly than gel without genipin (Likhitpanichkul et al, 2014;Likhitpanichkul et al, 2015), and the use of genipin crosslinking has been shown to alter several mechanical parameters (Fujii et al, 2020) and may be advantageous in treating disc pain (Guterl et al, 2013;Guterl et al, 2014;Peng et al, 2020) and disc degeneration (Yu et al, 2021). Thus, we tried genipin and tested Fib-T-G (F140 G6) gel as the best consistency for biocompatibility and adhesive strength; afterward, we applied this biological glue to repair the caudal AF slit injury of rats.…”
Section: Discussionmentioning
confidence: 99%
“…All SD rats were obtained from the Animal Center of Naval Medical University (Shanghai, China), and all procedures were approved by the Institutional Animal Care and Use Committee of the Naval Medical University. The extraction and identification of ADSCs were performed as reported in our previous study [ 28 ]. The third passage (P3) ADSCs were used for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…166–169 In the field of bioengineered repair of IDD, genipin is a commonly applied natural cross-linking agent that is used to increase the mechanical properties of dECM hydrogels to mimic the mechanical properties of natural IVDs. 140,141,143,145,148 Yu et al 148 found that when the genipin concentration was 0.02%–0.04%, the elastic modulus of dECM was close to that of human NP, which was more conducive to the recovery of IVD height. The majority of ADSCs cultured on dECM hydrogels at low genipin concentrations (0%–0.02%) survived.…”
Section: Application Of Decm In Iddmentioning
confidence: 96%
“…The modulus of elasticity values for normal human NP range from 7–20 kPa. 154 To increase the mechanical properties of dECM hydrogels, Yu et al 148 used genipin to cross-link dECM hydrogels and found that the elastic modulus of the hydrogels increased as the concentration of genipin increased and that the hydrogels had a similar elastic modulus to that of normal NP at a concentration of 0.02% genipin (10.70 ± 0.28 kPa). Zhou et al 140 similarly concluded that the G ′ and G ′′ values of dNP hydrogels were significantly lower than those of normal NP when the frequency was 10 rad s −1 .…”
Section: Application Of Decm In Iddmentioning
confidence: 99%